ANALISIS PEMBANGUNAN DESA WISATA BERKELANJUTAN BERBASIS COMMUNITY BASED TOURISM MELALUI COLLABORATIVE GOVERNANCE (STUDI KASUS: WISATA TEKNOLOGI HIDROGANIK DESA MOJOREJO) - Fawaid, Fawaid; M Fauzan Firjatullah; Dr. Hayat, S.A.P., M.Si (CV SWA Anugerah, 2025)
Specifically, this article aims to analyze the effectiveness of the programs that have been conducted by the Batu city government in addressing sustainable village development. This research also aims to identify the obstacles faced by the Batu City government in the development of tourist villages and provide recommendations to improve the programs that have been carried out. This research uses a qualitative approach method, which is a process of inquiry (questioning/investigation) regarding the understanding of a matter to obtain data, information, text of respondents' views using various methodologies in a social or humanitarian problem or phenomenon. In this article has two conclusions, First, the concept of this Hydroganic Technology Tourism is the management of organic crop agriculture and red tilapia fish farming collaborated with technology. Second, the Hydroganic Technology Tourism in Mojorejo Village explores how the implementation of hydroganic technology can support sustainable development goals.